Taking stock of an idiom’s background assumptions: an alternative relevance theoretic account - Noveck, Ira A.; Griffen, Nicholas; Mazzarella, Diana (Frontiers in Psychology, 2023)
This paper begins by presenting the theoretical background of, and the accompanying psycholinguistic findings on, idiom processing. The paper then widens its lens by comparing the idiom processing literature to that of metaphor and irony. We do so partly to better understand the idiom superiority effect, according to which idiomatic sentences (unlike metaphoric and ironic ones) are generally processed faster than their literal controls; part of our motivation is to reconcile the differences between idiom processing, on the one hand, and metaphor and irony processing on the other. This ultimately leads us to Relevance Theory (RT), which has provided original insights into the processing of figurative language generally, but especially with respect to metaphor and irony.RT has paid less attention to idiomatic expressions (such as break the ice, fan the flames, or spill the beans), where one finds a single RT account (Vega-Moreno, 2001) that likens idioms to conventional metaphors. Through our overview, we ultimately arrive at an alternative RT account of idioms: We argue that idioms include a procedural meaning that takes into account relevant presuppositional information. For example, an idiomatic string such as break the ice not only asserts initiate social contact, it prompts the recovery of background assumptions such as there exists a social distance that calls for relief. This leads us a) to apply linguistic-intuition tests of our presuppositional hypothesis, and; b) to describe the paradigm and results from a pilot experiment.Both provide support for our claims. In doing so, we provide an original explanation for the idiom superiority effect.